(untitled) (Journal of Libya for geographical studies, 2022)
Wadi Al-Dhabab basin, which is about 3 km from Taiz city, is the third most populated city in Yemen, the food basket of the city’s population. The basin is now considered one of the most important areas providing water for people after the water depletion that took place in the basins of Al-Hayba, Al-Hawban and Al-Hojala; Therefore, must there be a policy to enable the utmost benefit possible from harvesting rainwater; hence, ensuring ground and surface water sustenance and maintaining agricultural production in the basin. Thus, the research aims to build a spatial, fitting model that determines the most suitable locations for rainwater harvesting in the basin, by merging several criteria such as geological structure, geomorphological characteristics, slope, soil, drainage system, rainwater, depth of runoff, covers and land uses, and distance from residential areas and roads using GIS. Applying the mentioned criteria, the outcome of this model aims to obtain an informatics layer demonstrating the most suitable areas for rainwater harvesting; in addition, determining the quality of water harvesting systems in the basin using IMSD method is subsequently administrated. Accordingly the results showed that the area for suitable water harvesting location is 2.84 km2, rate 1.9%, and the area of an average suitable location is 109.8 km2, rate 74%, meanwhile, the area of a less suitable water harvesting location is 35.8 km2, rate 24.8% total of the basin.